Looking Again: Violence, Photography, Spectatorship, and Conflict Images of Children - Lewis, Christopher Dennis (Curtin University, 2016)
This thesis examines questions of photographic violence, ethics and spectatorship. It focuses these questions through images of children in situations of war and conflict. The thesis pursues several interrelated elements of the spectatorial relationship: context, presentation, temporality, photographic technologies and ethics. At the core of the thesis is the imperative to look beyond the first glance - which, in the case of violent, confronting images where children are involved, often forces us to look away.